The Efficacy of Adjuvant Chemoradiotherapy in Early-Stage Gallbladder Adenocarcinoma Depends on the Tumor Invasion Depth and Differentiation Level - Liang, Hui; Wang, Yifan; Chen, Jie; Xing, Jiajun; Pu, Yabin (Frontiers in Oncology, 2020)
Background Although the perfomance of adjuvant chemoradiotherapy (ACRT) for resected gallbladder cancer may improve the survival for certain patients, its impact on the survival in early-stage resected gallbladder adenocarcinoma (GBAC) patients remains underexplored. This study aimed to determine the ACRT effects on the survival of early-stage resected GBAC patients. Methods Patients with early-stage resected GBAC diagnosed between 2010 and 2016 were selected from the Surveillance, Epidemiology, and End Results (SEER) database. The covariables included gender, age, race, tumor differentiation, TNM stage (AJCC TNM staging system, 7th edition), adjuvant radiotherapy (ART) and adjuvant chemotherapy (ACT). The effects of ACRT on survival were evaluated by univariate and multivariate analysis. Results A total of 1,586 patients with resected GBAC met the inclusion criteria were included in this study. Patients who received ACT were older, with poorer tumor differentiation or higher TNM stage (all p < 0.05), while patients who underwent ART were proved to be significantly correlated with poorer tumor differentiation (p=0.010) and higher TNM stage (p<0.001). Univariate and multivariate analysis of overall survival (OS) showed that age (p < 0.001; HR, 2.039; 95% CI, 1.718–2.420), tumor grade (p < 0.001; HR, 1.887; 95% CI, 1.530–2.370) and AJCC 7th TNM stage (p < 0.001; HR, 1.417; 95% CI, 1.182–1.699) were independent prognostic risk factors. Interestingly, ART and ACT were not independently associated with improved OS in the overall cohort analysis. However, when patients were subgrouped according to tumor differentiation, ART (p = 0.049; HR, 0.639; 95% CI, 0.409–0.999) has been identified as a significant prognostic factor for grade III/IV patients. Meanwhile, ARC (p = 0.011; HR, 0.739; 95% CI, 0.586–0.932) was associated with improved OS among tumor stage II patients (p<0.001). Conclusion ACRT may have specific survival benefits for early-stage resected GBAC patients. ART can improve survival in patients with poor or absent tumor differentiation. Besides, patients with tumor invasion beyond muscularis (stage II tumor) may benefit from ACT. Our study provides supporting evidence for the clinical applications of ACRT in early-stage GBAC patients.